LACTIC ACID AND HYDROGEN PRODUCTION FROM MICROALGAL BLOOM BIOMASSES - Susilaningsih, Dwi -; Harahap, Puspita Sari; Farida, Hilda -; Rahman, Delicia Yunita (LIPI Press, 2017)
Microalgal bloom occurrence is rapidly increasing in a very short time in a specific condition and dominating its habitat. Therefore, blooming often occurs in water ecosystems, from freshwater to brackish and marine. Although there is no officially acknowledged threshold concentration level, the amount of algae cells is estimated reaching hundreds or even thousands cells per mililiter, depending on the species and types. Algae blooming is considered harmful because it gives such a big impact varies on water ecosystems, depending on the species involved, the environment where they are found, and their mechanism metabolism. The hazardous algae poison causes severe effect to various species, such as mammals and other sea creatures, with each presenting specific toxicity in decreasing motor development, immunology, neurological capacity, and reproduction capacity.In this report, the tropical algal bloom biomasses were used for fermentation substrate as substituent of carbon sources in purpose to produce a useful compound of lactic acid. Lactic acid is base material used in forming polylactic acid (PLA) polymerase that is known as basic material for biohydrogen precursor. The lactate bacteria were isolated from local tropical fruit.The result showed all microalgal biomasses converted successfully into lactic acid for 68–92% based on total carbohydrates conversion into lactic acid compounds. Algal bloom biomasses contained mostly of carbohydrate complexes (60–70% of dry weight), protein (10–20% of dry weight), lipid (20–30% of dry weight), and other compounds (5–10% of dry weight). The fermentation result showed that various microalgal blooms biomasses were successfully converted into lactic acid ranging from 58–92% based on total carbohydrates conversion into lactates. Furthermore, the obtained lactic acid was converted into polylactic acid through direct polycondensation process with average result of 60–84% formation unit base on lactic acid weight. Therefore, lactic acid was also successfully converted into hydrogen gas using fermentation process with efficient value from 78–90% unit based on the weight of lactic acid molecules. All these results showed that the unuseful algal biomass could be utilized as a substrate or precursor of fermentation process in term of biodegradable material and energy production, and also lactic acid is an applicable compound in forming polymers and energy.